Manajemen Nilai-nilai Islami dalam Kehidupan Rumah Tangga Miskin di Malang - Multifiah - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This research is aimed at discovering implementations of culture/ Islamic values like faith, understanding & behaviour on ZIS, and knowledge about poverty toward behaviour of extreemly poor families of Malang regency. Results of this research indicates that there is inconsistency between respondent’s understanding about culture/Islamic values with their implementations in daily lives. Scores of faith, understanding & behaviour on ZIS and high knowledge about poverty, do not exist in their real lives. Theoritically, the higher score of culture/Islamic values a man has the more productive he is. Practically income of respondents having representation of productivity lies below both minimum wages and Malang average income. This means that religion knowledge has no influence on their economic traits (as an evidence of their obeydience to Allah), they should be more productive for hard work represents the highest Islamic score in the presence of Allah SWT.Keywords: Baitul Maal, zakah, infaq, shadaqah, mustahik, muzakki, taqwa